The infectivity of single flagellates of Trypanosoma cruzi - P.D. Marsden; S.K.K. Seah; H. Lecherman (Revista da Sociedade Brasileira de Medicina Tropical, 1977)
Single organisms of Trypanosoma cruzi of the virulent Peru strain were isolated by direct visualisation and were injected peritoneally into CFI mice. Single trypanomastigotes of different morphology and from different sources (mouse blood, in vitro cufture and bug faeces) were used. Single trypanomastigotes from mouse blood caused parasitaemia and fataiity in a high percentage of mice. This was true irrespective of the morphology (broad or narrow form) of the trypano mastigo tec. Single organisms of the culture forms were also capable of causing infection, although these were less infectious than single trypanomastigotes obtained from mouse blood or the reduviid bug. The difficulties attendant on the performance of the cloning technique are discussed and some indication is given of how these problems can be overcome.